Respuesta :

Answer:

9

Step-by-step explanation:

6x - 3 + 3x = 60 + 2x

Combine like terms:

6x - 3 + 3x = 60 + 2x

9x - 3 = 60 + 2x

-2x                -2x

-----------------------

    7x - 3 = 60

         +3    +3

    ------------------

         7x = 63

        -----   -----

          7       7

            x = 9

Hope this helped.

Answer:

9

Step-by-step explanation:

to solve this equation you first have to group the like terms

6x-3+3x=60+2x

6x+3x-2x=60+3

7x=63

then you divide both sides by 7 inorder to remain with the variable x on one side

7x/7=63/7

x=9

I hope this helps